2020
DOI: 10.1101/2020.01.24.916783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aphid feeding induces the relaxation of epigenetic control and the associated regulation of the defense response inArabidopsis

Abstract: Environmentally induced changes in the epigenome help individuals to quickly adapt to fluctuations in the conditions of their habitats. Here we explored those changes in Arabidopsis thaliana plants subjected to multiple biotic and abiotic stresses, and identified transposable element (TE) activation in plants infested Gao LL, Kamphuis LG, Kakar K, Edwards OR, Udvardi MK, Singh KB (2010) Identification of potential early regulators of aphid resistance in Medicago truncatula via transcription factor expression p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Consequently, immune activation by biotic stress is associated with widespread loss of DNA methylation (hypomethylation) at TE-rich regions, while mutations reducing global DNA methylation increase biotic stress resistance (Dowen et al, 2012;Atighi et al, 2020;Annacondia et al, 2021). This link between plant immunity and TE hypomethylation can be explained by the discovery that immune activation leads to transcriptional repression of genes encoding RdDM components.…”
Section: Stage 1: the Regulatory Role Of Pathogen-induced Epigenetic Changementioning
confidence: 99%
“…Consequently, immune activation by biotic stress is associated with widespread loss of DNA methylation (hypomethylation) at TE-rich regions, while mutations reducing global DNA methylation increase biotic stress resistance (Dowen et al, 2012;Atighi et al, 2020;Annacondia et al, 2021). This link between plant immunity and TE hypomethylation can be explained by the discovery that immune activation leads to transcriptional repression of genes encoding RdDM components.…”
Section: Stage 1: the Regulatory Role Of Pathogen-induced Epigenetic Changementioning
confidence: 99%
“…5). Interestingly, a recent report showed that GER5 is overexpressed with CHH hypomethylation in response to aphid feeding and is also constitutively activated in suvh4 / kyp background, suggesting that GER5 altTE-Gi may contribute to the defense response and resistance to aphids 75 .…”
Section: Discussionmentioning
confidence: 99%